PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 1 SD - Selly Maria Margaretha; Viva Kafita; Diana Ernawati; Abdul Lathif, Muhammad Ichsan; Alfin Noor Aini (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This research was motivated by the low learning outcomes of class I students at SD N 04 Gondangmanis in learning. The purpose of this study was to determine student learning outcomes before and after using audio-visual-based learning media methods on first grade mathematics learning outcomes at SD N 4 Gondangmanis. This research is a quantitative research using experimental research methods. This study used an experimental method, and as a research plan used the Pre-Experimental Design Type One Group Pretest-Posttest Design. This study used pre-test before treatment and post-test after treatment. The population of this study were 15 first grade students of SD N 04 Gondangmanis. From the results of data collection techniques with tests, interviews, and documentation. The data analysis used in this study was normality test, hypothesis test, and t test (Paired T test) using SPSS 23. The results of the t-test (Paired T test) obtained sig. (2 tailed) of 0.00<0.05. It can be concluded that there is an influence of audio-visual-based learning media on the learning outcomes of class I mathematics at SD N 4 Gondangmanis. From these calculations, the results of the T test were found to be less than the significant level. This is also evidenced by the average pre-test of (60.6) and the average post-test score of (85.3).